The Ecology and Evolutionary History of an Emergent Disease: Hantavirus Pulmonary Syndrome - Yates, Terry L.; Mills, James N.; Parmenter, Cheryl A.; Ksiazek, Thomas G.; Parmenter, Robert R.; Vande Castle, John R.; Calisher, Charles H.; Nichol, Stuart T.; Abbott, Kenneth D.; Young, Joni C.; Morrison, Michael L.; Beaty, Barry J.; et al. (Bioscience, 2002)
Evidence from two El Nino episodes in the American Southwest suggests that El Nino-driven precipitation, the initial catalyst of a trophic cascade that results in a delayed density-dependent rodent response, is sufficient to predict heightened risk for human contraction of hantavirus pulmonary syndrome.